Pendampingan Tata Kelola Laboratorium Fisika SMA/SMK di Kota Pekanbaru melalui Kolaborasi Perguruan Tinggi dan Sekolah - Syahputra, Romi Fadli; Husna, Rofiqotul; Dalimunthe, Latipa Hannum; Lestari, Dinda; Rahmadani, Nofia; Fahturrahman, Fauzan; Fitri, Yulia; Retnawaty, Sri Fitra; Wirman, Shabri Putra; Fitrya, Neneng; Ginting, Delovita; Badrun, Yeeri; Gesriantuti, Novia; Herlina, Noftripa (LPPM UMRI, 2026)
This community service programme aimed to strengthen physics laboratory management and practical activities at three senior and vocational secondary schools in Pekanbaru, Indonesia. Conducted by lecturers and students of the Physics Study Programme, Universitas Muhammadiyah Riau, the programme involved partner assessment, orientation, implementation, and evaluation. Activities included developing Standard Operating Procedures (SOPs), inventorying laboratory equipment, preparing practical modules based on real experiments and PhET virtual simulations, and conducting practical training. Programme outcomes were evaluated through questionnaires administered to students and supervising teachers. Before the programme, 60% of students had never participated in physics practical activities. Following the intervention, all students (100%) reported improved understanding of the practical materials, with 20% reporting very good understanding, 33.3% good understanding, and 46.7% adequate understanding. Furthermore, 93.3% of students expressed positive attitudes towards physics practical activities and actively participated in recording and maintaining laboratory equipment. The programme also supported the development of students’ soft skills, particularly communication, collaboration, and leadership. Overall, the programme demonstrated the potential of university–school collaboration to strengthen laboratory management, enhance physics learning experiences, and provide a sustainable partnership model supporting the implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) policy.